Healthy Living: Changing your lifestyle to improve your blood pressure: FCS8885/FY1129, rev. 2/2018 - Shelnutt, Karla P.; Bobroff, Linda B. (EDIS, 2018)
Most people know that high blood pressure can often be improved by making smart dietary choices and choosing foods lower in sodium. But did you know there are other ways to help control high blood pressure and even prevent it? This 4-page fact sheet is a major revision that discusses four lifestyle changes that can help you keep blood pressure down. Written by Karla P. Shelnutt and Linda B. Bobroff, and published by the UF/IFAS Department of Family, Youth and Community Sciences, revised February 2018. http://edis.ifas.ufl.edu/fy1129